Associations of HLA-A and HLA-B with vancomycin-induced drug reaction with eosinophilia and systemic symptoms in the Han-Chinese population - Wang, Chuang-Wei; Lin, Wei-Chen; Chen, Wei-Ti; Chen, Chun-Bing; Lu, Chun-Wei; Hou, Hsin-Han; Hui, Rosaline Chung-Yee; Wu, Jennifer; Chang, Chih-Jung; Chang, Ya-Ching; Chung, Wen-Hung; , Taiwan Severe Cutaneous Adverse Reaction Consortium (Frontiers in Pharmacology, 2022)
Vancomycin is a commonly used antibiotic; however, it can cause life-threatening severe cutaneous adverse reactions, such as drug reaction with eosinophilia and systemic symptoms (DRESS). A previous study has reported a strong association between HLA-A*32:01 and vancomycin-induced DRESS in European ethnicity. Herein, we aim to investigate the genetic predisposition of vancomycin-induced DRESS in the Han-Chinese population. In this study, we enrolled a total of 26 patients with vancomycin-induced DRESS, 1616 general population controls, and 51 subjects tolerant to vancomycin. In vitro granulysin-based lymphocyte activation tests (LAT) were conducted among 6 vancomycin-induced DRESS patients who were concomitantly receiving other medicines. HLA-A and HLA-B genotypes were determined by sequencing-based typing. Our results found that vancomycin-induced DRESS was associated with HLA-A*32:01 (odds ratio (OR)=7.8, 95% confidence interval (CI)=1.7~35.8; P-value=0.035), HLA-B*07:05 (OR=32.3, 95% CI=2.8~367.7; P-value=0.047), HLA-B*40:06 (OR=4.7, 95% CI=1.3~16.1; P-value=0.036) and HLA-B*67:01 (OR=44.8, 95% CI=7.2~280.4; P-value=0.002) when comparing the vancomycin-induced DRESS patients with the general population controls. LAT results showed that granulysin significantly increased in the vancomycin-induced DRESS patients upon vancomycin stimulation (4.7±3.7 fold increased), but not upon other co-medicines. This study identified that, in addition to HLA-A*32:01, HLA-B*07:05, HLA-B*40:06 and HLA-B*67:01 were also genetic markers for vancomycin-induced DRESS in the Han-Chinese population. Associations of ethnic variances in HLA with vancomycin-DRESS were observed.